Följdeffekter av olika användningssätt för vedråvara - Götherström, Markus (2007)
Since the turn of the millennium a sharp increase in the interest for bio energy has been observed. Important reasons for this growing interest can be due to the fact that fossil fuels are a finite resource. A net discharge of greenhouse gases occur when fossil fuels are burned. The discharge of greenhouse gases are considered to be the main reason to the greenhouse effect. Means of control to increase the use of bio energy has been introduced and, as intended, the use of bio energy has increased.